PENINGKATAN KETERAMPILAN MENULIS TEKS BERITA MELALUI PENDEKATAN KONTEKSTUAL SISWA KELAS VIII H SMP NEGERI 4 TAMBANG KABUPATEN KAMPAR - Elvi Syahraini; Atmazaki .; Hasnah Faizah (Bahasa, Sastra, dan Pembelajaran, 2014)
Abstract: Writing skill needs to be taught to students in schools so that they have the ability to make a good news item texts. However, based on preliminary observations found that the students' writing achievement is low. Based on the results of 38 students found only 24 students get minimum criterion score (KKM). It is due to the use of learning strategies and media. Therefore, this study was conducted to describe the process of improving the students writing skill of the news item texts and describing the factor that cause of improvement the students writing skill of news item texts through Contextual Teaching and Learning (CTL) of eight grade students in SMP Negeri 4 Tambang Kampar Regency. This research was conducted in two cycles, each cycle performed in 2 meetings, one meeting for learning and one session for a test. The data were analyzed qualitatively and quantitatively. Qualitative analyze based on the teacher’s and student’s activity while quantitative data based on the results of tests. News item texts through contextual modeling component aids can be used as a means to create students’ imagination related to the natural view that will be written into news sentences. The writing skill of the news item texts at grade VIII H Tambang, Kampar Regency gets improvement after using contextual modeling component. While the factor cause of improvement the student’s writing skill of the news item texts are (1) take the writing practice by continually (2) the news model texts that giving to the students (3) approach of learn that teacher uses, and (4) observation activity. So, such activity could create the learning efficiency and effectiveness. CTL approach demands on students actively and work in groups cooperatively to optimalize learning outcome. The results of formative test showed that in cycle I gained 2,3 % the percentage of minimum criterion score. The further percentage of minimum criterion score in second cycle is increased 11,2 %. The results of this study proved that the writing skill of the news item texts at grade VIII H Tambang improved after using through CTL approach.   Kata Kunci: Keterampilan Menulis Teks Berita, Pendekatan Kontekstual (Contextual Teaching and Learning)